Les bovins trypanotolerants. Leur elevage en Republique Centrafricaine - Desrotour, J.; Finelle, P. (1967)
Note on the rearing of trypanotoletant humpless cattle in Central African Empire. Data on breeding with imported sire in trypanosomiasis infected areas included.